2017
DOI: 10.1007/s10518-017-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of structural damage detection methods for steel structures using full-scale experimental data and nonlinear analysis

Abstract: Rapid structural damage assessment methodologies are essential to properly allocate emergency response and 8 minimize business interruption due to downtime in the aftermath of earthquakes. Within this context, data-driven 9 algorithms supported by sensing capabilities can be potentially employed. In this paper, we evaluate an extensive 10 number of damage indicators computed based on nonmodel-based system identification techniques and wavelet 11analysis. The efficiency of these indicators to infer the damage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This may last weeks or months, accompanied with an important economic cost due to shut down. Modern structural health systems can provide real time damage detection based on changes in dynamic properties of the monitored structures [16]. There is a variety of methods both in time and frequency domain such as autoregressive methods, stochastic subspace identification, frequency domain decomposition method, which can assess the seismic performance and health condition through different indicators [17].…”
Section: Implementation Of Health Structural Monitoring System On Demonstration Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may last weeks or months, accompanied with an important economic cost due to shut down. Modern structural health systems can provide real time damage detection based on changes in dynamic properties of the monitored structures [16]. There is a variety of methods both in time and frequency domain such as autoregressive methods, stochastic subspace identification, frequency domain decomposition method, which can assess the seismic performance and health condition through different indicators [17].…”
Section: Implementation Of Health Structural Monitoring System On Demonstration Facilitiesmentioning
confidence: 99%
“…Moreover, the existence of a geotechnical seismic sensor close to the monitored facilities, allows the application of either output only or input/output methods [18]. For different structural types, different types of damage indicators may be more effective [16]. The functionality of the measurement chain, selected damage indicators and assessment methods will be verified in scaled benchmark structures and substructures in laboratory in advance.…”
Section: Implementation Of Health Structural Monitoring System On Demonstration Facilitiesmentioning
confidence: 99%
“…Noh et al [18] introduced the wavelet-based DSFs as structural damage indicators, which are defined by the ratio of the wavelet energy at the first-mode natural frequency of the building over time to the total wavelet energy. Hwang and Lignos [22] suggested that this wavelet-based DSF should be adjusted in cases that higher mode contributions become considerable. In this case:…”
Section: Wavelet-based Damage-sensitive Features For Structural Damagmentioning
confidence: 99%
“…Hwang and Lignos [22] conducted further validations on the potential use of wavelet-based DSFs for structural damage identifications based on full-scale shake table experiments on steel frame buildings with steel MRFs [24,25] and concentrically braced frames [26,27]. They found that the mapping of a DSF value to a story-based EDP is possible.…”
Section: Wavelet-based Damage-sensitive Features For Structural Damagmentioning
confidence: 99%
“…Hwang and Lignos 56 have numerically and experimentally identified the damage of a steel moment-resisting structure and a concentrically braced frame structure under sequence-based earthquakes. It was found that increasing earthquake intensities and structural damages result in decreasing the structural frequency.…”
Section: Introductionmentioning
confidence: 99%